2016
DOI: 10.1108/ijse-04-2014-0072
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing poverty and culture; towards a social economy of community centered knowledge based development

Abstract: Purpose – The purpose of this paper is to explore the critical interrelationships between poverty, culture and knowledge-based community development. Design/methodology/approach – The traditional approaches to the management of poverty such as infrastructure, literacy and economic aid have failed to deliver and ameliorate the lot of common people. The current paper engages in critical constructivist discourse on poverty as unfolding in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This was mainly because our study population was drawn from a private sector, non-unionised organization. Also, in Pakistan, industrial relations are conducted differently compared to the U.S. and other western countries, since the union's role is very limited, with only 3.4 percent of the labour force being unionised (Raza et al, 2016). However, since employees are becoming increasingly more sensitive to how their organization responds to external stakeholders, examining how and if PJ fit influences employees' external HR attributions in future research might prove fruitful.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This was mainly because our study population was drawn from a private sector, non-unionised organization. Also, in Pakistan, industrial relations are conducted differently compared to the U.S. and other western countries, since the union's role is very limited, with only 3.4 percent of the labour force being unionised (Raza et al, 2016). However, since employees are becoming increasingly more sensitive to how their organization responds to external stakeholders, examining how and if PJ fit influences employees' external HR attributions in future research might prove fruitful.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This was mainly because our study population was drawn from a private sector, non-unionised organization. Also, in Pakistan, industrial relations are conducted differently compared to the US and other western countries, since the union's role is very limited, with only 3.4% of the labour force being unionised (Raza et al. , 2016).…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Studies have previously shown that traditional approaches to managing poverty have failed to better the lives of poor communities (Raza et al, 2014). Further, the World Summit on Social Development in 1995 called for approaches that promote universal access to economic opportunities, as well as mainstreaming and democratic participation of poor communities in socio-economic activities within a country (United Nations Department of Economic and Social Affairs UNDESA, 1995).…”
Section: Sustainable Livelihoods and Poverty Eradiation Approach In Africamentioning
confidence: 99%